Aqiqah in Hadith Perspective - Agung Septiana; Deni Miharja (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to provide knowledge as well as refresh memory about understanding aqiqah from the perspective of hadith. This research method is qualitative by applying literature study. The research was carried out by collecting library sources, both primary and secondary. The results and discussion of this study include the understanding, terms and laws, arguments and slight differences of opinion between Imam Syafi'i and Imam Malik regarding aqiqah. This study concludes that aqiqah is a slaughtered animal that is slaughtered on behalf of a newborn baby on its seventh day as an expression of gratitude to Allah SWT. for His favors and gifts in the form of a child.